Effect of silver nanoparticles in microalgae dual bioreactor; 2nd International Symposium on Nanoscience and Nanomaterials SINN, Ensenada, Baja California, Mexico, March 4-8, 2012, CNyN-UNAM, "Welcome to the Bionanotechnology Group" - Meza A. V.; Lozano A. Y. V.; Vazquez R. M.; Bogdanchikova N.; Burmistrov V.; Pestryakov A. N. Aleksey Nikolaevich (2013, 2013)
В фонде НТБ ТПУ отсутствует